Susceptibility of Chicken Embryos, Sheep, Cattle, Pigs, and Chickens to Zika Virus Infection - Ambagala, Aruna; Truong, Thang; Cottam-Birt, Colleen; Berhane, Yohannes; Gerdts, Volker; Karniychuk, Uladzimir; Safronetz, David; Babiuk, Shawn (Frontiers in Veterinary Science, 2020)
The susceptibility of sheep, cattle, pigs, chickens and chicken embryos to Zika virus infection was evaluated by experimental inoculation with Zika virus Thailand strain isolated from a Canadian traveler in 2013. The inoculated animals did not develop any clinical signs of disease nor evidence of Zika virus replication in peripheral blood, cerebrospinal fluid and tissues including brain and spinal cord assessed by real-time RT-PCR. Sera were also negative for Zika virus antibodies by Zika virus neutralization assays as well as Zika virus immunoperoxidase staining of Zika infected Vero cells. Chicken embryos were inoculated by different routes including yolk sac (4 day old embryos), chorioallantoic membrane (8 day old embryos), amniotic fluid (8 day old embryos) and intravenous routes (12 day old embryos). Virus replication in chicken embryos was observed in the brain and body tissues following intravenous (IV), yolk sac (YS), chorioallantoic membrane (CAM), and amniotic fluid (AF) inoculation routes. The highest mortality was observed in embryos inoculated via yolk sac. The dead embryos showed diffuse muscular haemorrhages. The yolk sac inoculated chicken embryos showed delayed hatching and displayed neurological signs immediately after hatching. These studies demonstrate that 8 week old sheep, 6 month old cattle, 4 week old pigs and 4 week old chickens are not susceptible to Zika virus infection when inoculated experimentally and therefore unlikely to pose a risk as Zika virus reservoirs. However chicken embryos are highly susceptible to Zika virus resulting in clinical disease of chicks after hatching. This study demonstrates that Zika virus has a tropism for embryonic tissue and that chicken embryos can be used as a model to study Zika virus replication and pathogenesis.